Exotic Citrus Diseases: Early Detection is the Solution to Protecting Florida Citrus - M. M. Dewdney; J. D. Burrow; O. Batuman; A. Levy; R. H. Brlansky (EDIS, 2019)
This illustrated trifold brochure  provides key information about Pseudocercospora fruit and leaf spot, sweet orange scab, citrus leprosis virus, citrus variegated chlorosis (CVC), and citrus tristeza virus (CTV) stem pitting. Includes contact information for UF/IFAS Extension citrus experts.